Where are we now? Practice-level utilization of nurse practitioners in comparison with state-level regulations. Issue 6 (June 2020) - Zwilling, Jana G.; Fiandt, Kathryn
ABSTRACT: Background and purpose: Full practice authority for nurse practitioners (NPs) is optimal for high-quality, cost-effective health care. However, a complete picture of utilization after states have adopted full practice authority needs to be determined. The purpose of this examination was to review the evidence regarding practice-level utilization (PLU) of NP PLU in comparison to state-level regulations (SLRs). Methods: Studies published in English and based on US populations were identified through PubMed, CINAHL, and Scopus (January 1, 1989–December 31, 2018), and bibliographies of retrieved articles. Of the 419 articles identified with these limits, 19 (5%) met all inclusion and exclusion criteria. Conclusions: Four categories of PLU were identified: billing practices, level of supervision, privileges, and prescriptive authority. Significant differences were seen between urban versus rural NPs and primary care versus specialty NPs. Thirteen of the 19 studies did not specifically address the SLR of the included sample. Implications for practice: No studies described the type of NP certification, practice specialty, and utilization, and compared all to the SLR. There is a need for more evidence concerning PLU of NPs across the tiers of SLR. Only then can health care organizations, political leaders, and other stakeholders have the information needed to proceed with beneficial practice-model changes.